Enhancing Entrepreneurial Performance Through Knowledge Management: Perspective in Education Sector in Indonesian - Indira, Syahda Sukma; ., Sasmoko; Bandur, Agustinus; Pradipto, Yosef Dedy (Journal of Posthumanism, 2025)
Entrepreneurship development is known to play a critical role in advancing and fostering progress within schools. Therefore, this paper aims to examine the direct effect of knowledge management on entrepreneurial performance as well as measure the mediating role of value co-creation in this relationship. For these purposes, an empirical survey was conducted with the active participation of 380 respondents, comprising of school principals, teachers, and school council members. The quantitative data sources were principals, teacher representatives, and committees. The results showed that knowledge management could improve entrepreneurial performance and value co-creation. In addition, value co-creation had no direct effect on entrepreneurial performance and did not mediate the influence of knowledge management on entrepreneurial performance.